PENGGUNAAN TEKNOLOGI PENGERING UNGGUN TERFLUIDISASI UNTUK MENINGKATKAN EFISIENSI PENGERINGAN TEPUNG TAPIOKA - Rizky Adi N; Nafiah Amalia; S Suherman; R Ratnawati (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Drying of cassava starch using conventional method has many disadvantages, such as longer drying time, totally dependent on good weather, and inconsistent product quality. It drives this research to develop fluidized bed drying technology which is more efficient and able to operate continuously. The advantages of fluid bed dryer include ease of control, good quality of product, and free of dirt. The objectives of this research are to determine the effects of temperature and velocity of drying air to the drying process and product. The drying products were compared to the products of conventional drying. The experiment was carried out at various temperature (30, 40, 50, and 60 oC) and air velocity (2.5, 3.5, and 4.5 m/s). The results indicate that the optimum temperature for drying is 50 oC, while the air velocity is 2.5 m/s. Proximate analysis shows that the product of fluidized bed drying has better quality than that of conventional sun drying.